Comprehensive assessment of heavy metal pollution in topsoil of historical urban park on an example of the Planty Park in Krakow (Poland). (July 2017) - Gąsiorek, Michał; Kowalska, Joanna; Mazurek, Ryszard; Pająk, Marek
Abstract: The Historic Centre of Krakow is on the UNESCO World Heritage List and includes the Main Market Square, which is surrounded by the historical Planty Park. Soils in the Planty Park are an example of a green area in an urban environment that is particularly exposed to heavy metal-rich pollution. To assess the relative content of heavy metals and evaluate the sources of the contamination, pollution indices were used: Enrichment Factor ( EF), Geoaccumulation Index (I geo ), Nemerow Pollution Index ( PI Nemerow ), Potential Ecological Risk ( RI ), and Contamination Security Index ( CSI ). Pollution indices were calculated on the base of both reference and local geochemical backgrounds. Sources of heavy metals in soils of Planty Park are related to its historic role as a metallurgy centre, as well as the more recent urban and industrial development of Krakow centre and neighbouring areas. It is concluded that increased accumulation of heavy metals is an effect of growing numbers of emission sources. The variation of each element may not unambiguously reflect the natural or anthropogenic effect on the Planty Park soil cover. In general, the present and historical emission of pollutants and heavy metal-rich contamination has led to a mixed origin of Cd, Cu, Pb, and Zn. Moreover, it can be assumed that the content of Cr and Ni is derived from natural sources. Furthermore, a comparison of the quality of the Planty Park topsoil with the heavy metal content assessment in other urban parks in the world has been presented. Graphical abstract: Highlights: Assessment of surface soil layer pollution of Planty Park in Krakow's Old Town was presented. Several pollution indices ( EF, I geo, PI Nemerow, RI, and CSI ) were used to comprehensively evaluate Planty Park's topsoil. Different sources of heavy metal pollution in urban park soils have been defined. Comparison of topsoil pollution between Planty Park and urban parks from selected cities around the World has been performed.